1994
DOI: 10.1016/0304-3959(94)90153-8
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of oral splints in the treatment of myofascial pain of the jaw muscles: a controlled clinical trial

Abstract: Oral splints are widely used in the treatment of myofascial pain of masticatory muscles, even though their mechanism of action is unknown. The present study evaluated the therapeutic efficacy of splints using a parallel, randomized, controlled and blind design. Following a sample size estimation, 63 subjects were recruited and assigned to 3 groups: (1) passive control: full occlusal splint worn only 30 min at each appointment; (2) active control: palatal splint worn 24 h/day; and (3) treatment: full occlusal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
2
20

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(152 citation statements)
references
References 50 publications
4
126
2
20
Order By: Relevance
“…However, two out of three other randomly controlled studies which have compared the stabilising splint with a non-occluding control have shown both appliances equally effective. 6,7 In these two studies patients were all diagnosed with myofascial pain. There has been only one study that showed the stabilising splint to be significantly better than a control splint.…”
Section: Comparison Of Stabilising Splint and Control At Six Weeksmentioning
confidence: 99%
“…However, two out of three other randomly controlled studies which have compared the stabilising splint with a non-occluding control have shown both appliances equally effective. 6,7 In these two studies patients were all diagnosed with myofascial pain. There has been only one study that showed the stabilising splint to be significantly better than a control splint.…”
Section: Comparison Of Stabilising Splint and Control At Six Weeksmentioning
confidence: 99%
“…Debido a que los dos grupos presentan la misma inervación por el V par craneal y una sintomatología similar, se vuelve complicado diagnosticarlos de manera independiente [9][10][11] . Los trastornos temporomandibulares como el síndrome de dolor miofascial se pueden presentar en articulaciones sin alteraciones previas y suelen ser el 50-75% de las causas de atención odontológica a nivel mundial [12][13][14][15] , por lo cual se considera un dolor común pero incomprendido que involucra el dolor referido por los puntos gatillo en el musculo esquelético 16,17 .…”
Section: Introductionunclassified
“…Acredita-se que seja uma condição de importância substancial na saúde pública com uma prevalência de aproximadamente 10% entre adultos (LERESCHE, 1997 LEEUW et al, 1994;DAO et al, 1994). O controle dos estudos pode ser realizado através de placebo, lista de espera controle ou controlados por não tratamento.…”
Section: Discussionunclassified
“…Outros efeitos incluem a eliminação ou alteração da influência da informação proprioceptiva nociva das interferências oclusais RIISE, 1986;MAZZETTO, 2008); redução ou modificação do padrão de atividade muscular noturna (SHEIKHOLESLAM; HOLMGREN; RIISE, 1986), e são ainda relatados, aumento da dimensão vertical (CHANDU et al, 2004) e efeito placebo (DAO et al, 1994;CAPP, 1999;RÉ et al, 2009;THURMAN;HUANG, 2009). …”
Section: Terapia Com Placas Oclusaisunclassified
See 1 more Smart Citation